Superconducting magnets and technologies for future colliders - Bottura, Luca; Prestemon, Soren; Rossi, Lucio; Zlobin, Alexander V. (Frontiers in Physics, 2022)
The implications of accelerator magnet R&D towards future colliders are reviewed and discussed. It starts with a brief overview of the present and future accelerator facilities which rely on the significant advances and innovations in key technologies. Then advances and needs for present key projects and studies are expanded on specific examples. This provides the lead to discuss the recent progress in accelerator magnet R&D and the future plans. We conclude with a summary of our view of the major development drivers and future perspectives.